2015
DOI: 10.1126/science.aac8653
|View full text |Cite
|
Sign up to set email alerts
|

Gate control of mechanical itch by a subpopulation of spinal cord interneurons

Abstract: Light mechanical stimulation of the hairy skin can induce a form of itch known as mechanical itch. This itch sensation is normally suppressed by inputs from mechanoreceptors, however, in many forms of chronic itch, including alloknesis, this gating mechanism is lost. Here we demonstrate that a population of spinal inhibitory interneurons (INs) that are defined by the expression of neuropeptide Y::Cre (NPY::Cre) act to gate mechanical itch. Mice in which dorsal NPY::Cre-derived neurons are selectively ablated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
290
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(319 citation statements)
references
References 39 publications
21
290
7
1
Order By: Relevance
“…In particular, such studies have demonstrated that molecular markers can define specific subsets of neurons of a particular sensory modality and that neurons that were previously thought to be similar based on anatomical connectivity can develop from different progenitor domains. For example, a GRPR + subset of the dI5/dIL B lineage is involved in chemical itch sensation and a NPY + subset of the dI4/dIL A lineage is involved in mechanical itch pathways, giving credence to the idea that there are distinct somatosensory submodalities that are integrated via distinct spinal microcircuits (Bourane et al, 2015a;Ma, 2012;Sun et al, 2009). However, neurons that have been defined by anatomical characteristics may arise from more than one developmental population.…”
Section: Connecting Developmental Identity To Functional Identity Witmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, such studies have demonstrated that molecular markers can define specific subsets of neurons of a particular sensory modality and that neurons that were previously thought to be similar based on anatomical connectivity can develop from different progenitor domains. For example, a GRPR + subset of the dI5/dIL B lineage is involved in chemical itch sensation and a NPY + subset of the dI4/dIL A lineage is involved in mechanical itch pathways, giving credence to the idea that there are distinct somatosensory submodalities that are integrated via distinct spinal microcircuits (Bourane et al, 2015a;Ma, 2012;Sun et al, 2009). However, neurons that have been defined by anatomical characteristics may arise from more than one developmental population.…”
Section: Connecting Developmental Identity To Functional Identity Witmentioning
confidence: 99%
“…Expression of Lhx1/5 is required for the NPY + fate, while expression of Neurod1/2/6 is required for the dynorphin-expressing (DYN + ) fate (Brohl et al, 2008). The NPY + dI4/dIL A lineage mainly in laminae III-IV has recently been shown to gate itch behaviors, specifically mechanical itch as opposed to chemical-evoked itch (histaminergic and non-histaminergic) (Bourane et al, 2015a) whereas the DYN + fate has been implicated in gating mechanical pain and chemical itch (discussed in the next section).…”
Section: Inhibitory Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress has advanced our understanding of molecular and cellular mechanisms of itch (Ji, 2018; LaMotte et al, 2014; Meixiong and Dong, 2017), including but not limited to the receptors of itch (Alemi et al, 2013; Liu et al, 2009; Liu et al, 2010; Wilson et al, 2013b), the neurotransmitters and neuromodulators of itch (Kardon et al, 2014; Mishra and Hoon, 2013; Sun and Chen, 2007), and especially the itch-mediating neurons and neurocircuits (Bourane et al, 2015; Han et al, 2013; Huang et al, 2018; Mishra and Hoon, 2013; Roberson et al, 2013; Ross et al, 2010; Sun et al, 2017; Sun et al, 2009). Primary sensory neurons especially nociceptors express TRPA1 for pain sensation and sensitization (Bautista et al, 2006; Patapoutian et al, 2009; Story et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Une population d'interneurones dorsaux exprimant GRPR, le récepteur au GRP (gastrin-releasing peptide), a récemment été identifiée comme intervenant dans le contrôle spinal des déman-geaisons chimiques [8][9][10] (➜). En utilisant un antagoniste de GRPR, ou en éliminant les interneurones GRPR+ qué dans le contrôle des démangeai-sons induites par des stimuli méca-niques légers, non douloureux [5]. des informations sensorielles du toucher léger émanant de la peau velue.…”
Section: Différents Circuits Spinaux Sont Impliqués Pour Les Démangeaunclassified